Assessment of Clinical Skills and Knowledge in Ophthalmology in Undergraduate Medical Students: Ophthalmology Competence Among Medical Students - Amna Rizwan; Muhammad Ali; Nida Khalid; Asfandyar Asghar (Journal of University College of Medicine and Dentistry, 2025)
Objective: To evaluate the self-perceived competence and exposure of undergraduate medical students to clinical skills and theoretical knowledge in ophthalmology. Methodology: A descriptive cross-sectional study was carried out at Fauji Foundation Hospital, Rawalpindi. A detailed online questionnaire was circulated amongst fourth-year medical students between October 2023 and February 2024 who had completed their end-of-year examination. We included in the analysis 189 out of 204 respondents who had fully completed the questionnaire. A validated, pilot-tested questionnaire with good internal consistency (Cronbach’s alpha = 0.82) was used to collect data on demographics, ophthalmology training exposure, clinical skills competence, ability to recognize ocular emergencies, surgical observation, and research participation. Results: A total of 189 students responded (mean age: 22.75 ± 0.84 years), two-thirds (66.7%) of which were female. Over 70% of students reported confidence in performing basic ophthalmic skills, including extraocular muscle function, visual acuity, pupillary examination, history taking, visual fields, and squint assessment. However, only 52.7% had hands-on exposure to direct ophthalmoscopy, and a mere 18% had participated in any ophthalmology-related research activities. Conclusion: The findings highlight a limited and uneven exposure to essential ophthalmic skills among undergraduate students. Key deficiencies, particularly in direct ophthalmoscopy and research participation, highlight the need for structured curriculum enhancements to improve clinical preparedness in ophthalmology.